سيميائية الصائت الواقع قبل نون التوكيد في القرآن الكريم - البكوش , نجاة سعد محمد (Scientific Journal of University of Benghazi, 2022)
Since the time of Sibawayh, early grammarians have differed in interpreting the change in the movement of letters occurring before the emphasizing nun (ن). Some modern scholars have attempted to analyse the syllabic construct of the nun of emphasis, and its effect on the present tense which it is used to confirm. Others rejected that analysis since earlier grammarians were aware of the effect of the emphasizing nun on the structure of the verb, as they were aware of other morphological suffixes that are attached to the structures of nouns and verbs in Arabic; Therefore, one of the objectives of this research was to present the efforts of grammarians in analyzing the effect of the emphasizing nun on the syntax letter, and to clarify the easiest ways in expressing the present tense confirmed by it, and to highlight the relationships between the type of movement before the nun of emphasis, and its quantity, and the semiotics of the Qur'anic context in which it was presented; i.e. between the phoneme and the context components. It appears that the phoneme before the emphatic nun is a linguistic marker; it has a function in the linguistic context, which varies from context to context. In each context, it interacts with the linguistic markers covered by the same context, producing connotations that reveal the intended meaning for the recipient. This is what makes each of the phonemes before the nun a special semiotic which varies from context to context and is appropriate for the linguistic markings that accompanied them in context.